The Cleveland Clinic way : lessons in excellence from one of the world's leading healthcare organizations - Cosgrove, Toby, 1940- (McGraw-Hill's AccessMedicine., 2014)
There's a revolution going on right now. On the frontiers of medicine, some doctors have developed an approach for treating people that is more effective, more humane, and more affordable. It's an approach to healthcare that has captured the attention of the media and business elite--and the President of the United States. It's all happening at Cleveland Clinic, one of the most innovative, forward-looking medical institutions in the nation. In this groundbreaking book, the man who leads this global organization, Toby Cosgrove, MD, reveals how the Clinic works so well and argues persuasively for why it should be the model for the nation. He details how Cleveland Clinic focuses on the eight key trends that are shaping the future of medicine. At its core is Cleveland Clinic's emphasis on patient care and patient experience. A refreshingly positive and practical vision of healthcare, The Cleveland Clinic Way is essential reading for healthcare and business executives, medical professionals, industry analysts, and policymakers. It gives leaders lessons they can apply to their own organizations to achieve results and empowers average Americans to make more informed healthcare decisions.